Receptiveness of Islamic home financing among Malaysians : a revisit - Muhammad Sayuti, Khadijah; Amin, Hanudin; Abdul Razak, Dzuljastri; Rizal, Hamid (Universiti Malaysia Sarawak, 2020)
This study examines the effects of the key factors influencing the intention of first-time house buyers to choose Islamic home financing products. First-time house buyers are selected since they are the major segment of Islamic banks' profit for the Islamic mortgage sector. Drawing upon the theory of planned behaviour (TPB), this study proposes a model to test the effects of attitude, subjective norm and perceived behavioural control on the intention of selecting Islamic home financing. This study also examines the effect of "perceived customer taqwa” on customer receptiveness to Islamic home financing. Based on 150 usable questionnaires, PLS results indicate that attitude and perceived behavioural control of the TPB are instrumental in determining the receptiveness of Islamic home financing products. Besides, the added factor, namely, perceived customer taqwa is influential in explaining the receptiveness- implying that God-fearing and God-conscious in oneself resulted in strong intention to opt for halal products. The findings demonstrate that the enhancement of measurement items for TPB factors as well as generation of new factor reflecting Islamic home financing are relevant in determining one’s decision of Islamic home financing. Besides, the findings could offer support to Islamic bank managers to enhance their planning for Islamic home financing products and develop effective strategies accordingly that benefit their customers.